The solid state structures of metallo-beta-amino alcohol complexes - Reisinger, Sandra Ann (My University, 2009)
The ligands N,N’-bis(2-hydroxycyclohexyl)ethylenediamine (Cy2-en), and 2,2’-[(hydroxypropane-1,3-diyl)diimino]dicyclohexanol (Cy2-Otn) are synthesised and their solid state structures determined by X-ray diffraction experiments. Complexes are formed with the metal ions Pb2+, Cd2+, Ni2+, and Zn2+. The solid state structures of the lead(II) complex of Cy2-en and the cadmium(II) complex of Cy2-en are determined by X-ray diffraction experiments. Further complexations of the Pb2+ and Cd2+ ions are attempted with N,N’-bis(2-hydroxycyclohexyl)-1,3-propanediamine (Cy2-tn), and N,N’-bis(2-hydroxycyclohexyl) diethylenetriamine (Cy2-dien). The reactions are not successful. The ligand N,N’-bis(2-hydroxyethyl)ethylenediamine (BHEEN) is reacted with the metal ions Pb2+, Cd2+, Ni2+, and Zn2+, and the solid state structures of the cadmium(II) complex of BHEEN and the zinc(II) complex of BHEEN are determined by X-ray diffraction experiments. The solid state structures of both the ligands as well as the complexes indicate the presence of hydrogen-hydrogen bonds. The complexes contain more interactions than the uncoordinated ligands. Attempts are made to relate the interactions to the observed log K values for the complexes. Molecular mechanics calculations are performed to ascertain if a simple MM approach can suitably predict the conformations of the free ligands as well as the cadmium(II) complex of Cy2-en. The conformations of the free ligands are predicted well but the cadmium(II) complex of Cy2-en cannot be predicted without the addition of cadmium parameters to the GAFF force field.